COMMUNITY-BASED DEVELOPMENT APPROACH IN MAKASSAR (Community Development, Community Empowerment, And Asset-Based Community Development/ABCD) - Ayu Indira Sangaji; Ernawati Arsyad; Najamuddin Najamuddin (Lembaga Penelitian dan Pendidikan Mandala, 2026)
Community-based development has become an important approach in addressing various social problems in urban communities, particularly in Makassar City, which has a high level of social heterogeneity. This article aims to analyze the implementation of the Community Development, Community Empowerment, and Asset-Based Community Development (ABCD) approaches in community development in Makassar. This study employs a descriptive qualitative approach using literature review and social observation methods toward community empowerment practices in urban areas. The findings indicate that community-based development is capable of increasing community participation, strengthening social capital, and creating community independence through the utilization of local assets. The ABCD approach is considered more adaptive because it positions the community as the subject of development with internal capacities and resources. In Makassar, the implementation of community-based development can be seen in waste bank programs, tourism alley programs, community-based micro, small, and medium enterprises (MSMEs), and women’s empowerment initiatives in densely populated areas. The main challenges include the lack of program sustainability, inequality in access to resources, and the dominance of top-down approaches in development policies. Therefore, a sustainable participatory development model based on local community potential is needed.